Platelet-Rich Plasma Injections Decrease the Need for Any Surgical Procedure for Chronic Epicondylitis versus Conservative Treatment-A Comparative Study with Long-Term Follow-Up - Annaniemi Juho Aleksi; Pere Jüri; Giordano Salvatore (MDPI, 2025)
Background: Platelet-rich plasma (PRP) injections may alleviate symptoms of chronic medial or lateral epicondylitis.
Methods: We retrospectively analyzed a total of 55 patients with chronic ME or LE who had undergone at least 6 months of any conservative treatment before intervention. The patients were divided into two groups: the PRP group (n = 25), who received a single injection of autologous PRP to the medial or lateral epicondyle, and the PT group (n = 30), who continued with PT and pain medication. The primary outcome measures were pain and functional outcomes measured in terms of the following: Patient Related Tennis Elbow Evaluation (PRTEE), Visual Analogue Scale (VAS), and Disabilities of the Arm, Shoulder, and Hand (DASH), which were detected at preintervention, 6-, 12-, 24-, and 36-month follow-up. Secondary outcomes included complications and the need for any surgery at follow-up.
Results: Primary outcome measurements showed significantly better results favoring the PRP group (6-month PRTEE total 43.2 ± 19.2 vs. 62.8 ± 24.0, p < 0.001; 12-month PRTEE total 6.9 ± 15.0 vs. 28.1 ± 24.4, p < 0.001; 24-month PRTEE total 4.8 ± 9.8 vs. 12.7 ± 14.5, p = 0.029), and significantly better results in VAS and DASH sub-scores. The PRP group required significantly fewer surgical procedures (n = 0/0% vs. n = 6/20%, p = 0.027) at follow-up (mean 38.3 ± 12.3 months), and one case of prolonged pain after injection was detected.
Conclusions: Patients who underwent PRP injections for epicondylitis resulted in better pain and functional outcomes compared to physiotherapy, and this improvement lasted at least 24 months. They required fewer surgical procedures and achieved faster recovery than the PT group. We recommend PRP for chronic epicondylitis of the elbow before considering surgery when other treatments have failed.